2016
DOI: 10.1136/annrheumdis-2016-eular.5439
|View full text |Cite
|
Sign up to set email alerts
|

AB0070 A Role of Synovial Exosomes in Osteoclast Differentiation of Inflammatory Arthritis

Abstract: BackgroundExosomes are small membrane vesicles (40–150 nm) of endocytic origin secreted by many types of cells and engage in cell-to-cell communication by transferring proteins, microRNAs, mRNA, and lipid to recipient cells. Exosomes are also identified in various biological fluids including blood, urine, amniotic fluid, saliva, malignant ascites, and synovial fluid. Until now, the role of exosomes from synovial fluid (SF) on human osteoclastogenesis is unknown.ObjectivesWe aimed to identify the characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Meanwhile, it also plays an important role for nutrient and waste transportation for chondrocytes (Valachová and Oltés, 2021). Currently, researchers have investigated the contents of EVs distributed in synovial fluid and found that EVs from OA synovial fluid showed a negative impact on the articular chondrocytes, inducing the promotion of macrophage proliferation and osteoclast formation as well as activating inflammatory cells (Song et al, 2016;Kolhe et al, 2017;Rossana et al, 2017). Incremental cargoes of EVs, such as miR-200C and LncRNA PCGEM1, from the synovial tissue and synovial fluid were identified in patients with joint diseases.…”
Section: Synovial Tissue and Synovial Fluidmentioning
confidence: 99%
“…Meanwhile, it also plays an important role for nutrient and waste transportation for chondrocytes (Valachová and Oltés, 2021). Currently, researchers have investigated the contents of EVs distributed in synovial fluid and found that EVs from OA synovial fluid showed a negative impact on the articular chondrocytes, inducing the promotion of macrophage proliferation and osteoclast formation as well as activating inflammatory cells (Song et al, 2016;Kolhe et al, 2017;Rossana et al, 2017). Incremental cargoes of EVs, such as miR-200C and LncRNA PCGEM1, from the synovial tissue and synovial fluid were identified in patients with joint diseases.…”
Section: Synovial Tissue and Synovial Fluidmentioning
confidence: 99%
“…Domenis et al found that synovial fluid-derived exosomes significantly stimulated the release of several inflammatory cytokines, chemokines and metalloproteinases by M1 macrophages [14] . Incubating macrophages with exosomes from synovial fluid of OA, Song et al demonstrated that the exosomes could induced proliferation and osteoclast formation without macrophage colony-stimulating factor (M-CSF) and receptor activator of nuclear factor kappa-B ligand (RANKL) [15] .…”
Section: Exosomes In Oa Pathologymentioning
confidence: 99%